2021
DOI: 10.1021/acs.chemmater.1c02101
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis-Regulated Chemical Bath Deposition of Tin-Oxide-Based Electron Transport Layers for Efficient Perovskite Solar Cells with a Reduced Potential Loss

Abstract: The high electron mobility, wide band gap, and chemical stability of n-type SnO2 have facilitated its use as an ideal electron transport layer (ETL) for perovskite solar cells (PSCs). However, the tendency of SnO2 to aggregate during film formation leads to poor morphology and low reproducibility. Despite important advances in the application of SnO2 for PSCs, a thorough understanding of material control over aggregation is lacking. Herein, aggregation-regulated SnO2 films are directly deposited on a fluorine-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 54 publications
0
27
0
Order By: Relevance
“…However, the SnO 2 -Li film has increased roughness as AFM indicated due to ultralarge micron particles. In Figure S4, it is found that exposed FTO is present in the SnO 2 film, which is verified by other researchers on SnO 2 films prepared at low temperatures. , Therefore, a better coverage of reconstituted SnO 2 -Na reduces the pinholes and cracks at the surface, which may resist leakage current and carrier recombination loss . Then, the transmission of SnO 2 films is measured in Figure S5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the SnO 2 -Li film has increased roughness as AFM indicated due to ultralarge micron particles. In Figure S4, it is found that exposed FTO is present in the SnO 2 film, which is verified by other researchers on SnO 2 films prepared at low temperatures. , Therefore, a better coverage of reconstituted SnO 2 -Na reduces the pinholes and cracks at the surface, which may resist leakage current and carrier recombination loss . Then, the transmission of SnO 2 films is measured in Figure S5.…”
Section: Resultsmentioning
confidence: 99%
“…30,31 Therefore, a better coverage of reconstituted SnO 2 -Na reduces the pinholes and cracks at the surface, which may resist leakage current and carrier recombination loss. 32 Then, the transmission of SnO 2 films is measured in Figure S5. SnO 2 -Na films cause no transmission loss.…”
Section: Resultsmentioning
confidence: 99%
“…This observation corroborates that the surface energy of the t-SnO 2 layers exerted at the perovskite layer is consistent for the heterojunction bilayers and possibly originates from the equivalent quality of the t-SnO 2 layers. [23] To elucidate the discrete behavior observed in the PSCs, dark J-V curves were investigated by performing fast J-V scans to obtain sheer electrical signals across a device without the slow time component, which may be related to ionic movement or a slow displacement of charge. [40] Figure 3a-d shows the dark J-V curves of the PSCs measured at a scan rate of 1000 mV s -1 .…”
Section: Resultsmentioning
confidence: 99%
“…[22] However, this technique is prone to generate an imperfect morphology with pinholes and cracks causing nonradiative recombination. [23,24] In contrast, bilayer structures appear competitive in terms of interfacial engineering for better charge extraction because of the passivation by a sequential layer synergically with enhanced band alignment. [25,26] Specifically, homojunction bilayers were sequentially constructed by depositing different SnO 2 layers.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the relatively slow deposition rates, an industrial CBD process has to be performed in parallel coating a large number of conductive oxide plates simultaneously. Recently, the deposition of SnO 2 using CBD has shown outstanding results for PSCs in terms of device efficiency (> 25%) as well as stability on both small cells ,, and mini-modules . This level of performance clearly demonstrates that SnO 2 is very well suited for being implemented into a perovskite device; however, the chemical mechanism that drives its deposition remains unclear.…”
Section: Introductionmentioning
confidence: 99%